Stability constant of some Metal Ion Complexes of (6-(2Amino-2-(4-hydroxy phenyl)-acetamido)-3,3–dimethyl-7oxo-4-thia-1-aza-bicyclo[3,2,0]heptanes-2carboxylicacid(Amoxicillin) - Sarhan, Basima M.; Kadhim, Nada J.; Wheed, Enas J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Measurement of stability constant of some complexes formed by (6-(2-amino-2-(4hydroxy phenyl)-acetamido)-3,3-dimethyl-7-oxo-4-thia-1-aza-bicyclo[3,2,0] heptanes-2carboxylic acid (Amoxicillin) with (Cr+3, Co+2, Ni+2, Cu+2,Ag+1, and Cd+2) ions, have been performed(Amoxicillin) was found to behave as bidentate ligand with ahardness parameter(Î±)of (0.46)and asoftness parameter(Î²)of (1.03) while complexes being formed were of (1:1)ratio.